2021
DOI: 10.1111/1365-2664.13888
|View full text |Cite
|
Sign up to set email alerts
|

How grazing management can maximize erosion resistance of salt marshes

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 80 publications
1
11
1
Order By: Relevance
“…The range of the Y-axis spans the elevation range where salt marshes occur (70-200 cm + NAP; Dijkema et al 2011) ◂ age-dependent autocompaction, whether or not dependent on livestock, but the effect of these terms (an increase in compaction by c. 0.13 cm year −1 ) appears to be smaller than the age-independent autocompaction estimated from the intercepts (c. 0.78 cm year −1 ). These findings are at variance with Elschot et al (2013) and Marin-Diaz et al (2021) who found a strong effect of trampling. Also, Nolte et al (2015) found a significant effect of livestock, at least under certain conditions (high precipitation, high inundation frequency).…”
Section: Precipitation Swelling Shrinkage and Compactioncontrasting
confidence: 40%
See 1 more Smart Citation
“…The range of the Y-axis spans the elevation range where salt marshes occur (70-200 cm + NAP; Dijkema et al 2011) ◂ age-dependent autocompaction, whether or not dependent on livestock, but the effect of these terms (an increase in compaction by c. 0.13 cm year −1 ) appears to be smaller than the age-independent autocompaction estimated from the intercepts (c. 0.78 cm year −1 ). These findings are at variance with Elschot et al (2013) and Marin-Diaz et al (2021) who found a strong effect of trampling. Also, Nolte et al (2015) found a significant effect of livestock, at least under certain conditions (high precipitation, high inundation frequency).…”
Section: Precipitation Swelling Shrinkage and Compactioncontrasting
confidence: 40%
“…The general effect of autocompaction is that older marshes, that have a thick clay layer, show a lower accretion rate than young marshes, irrespective of surface elevation (Cahoon et al 1995;Van Wijnen and Bakker 2001). Compaction may be further enhanced by trampling of livestock (Elschot et al 2013;Marin-Diaz et al 2021). We included terms for compaction that is dependent on both marsh-age (as a proxy for clay layer thickness) and the presence of livestock, but we also considered the intercepts of our models as estimates for age-independent autocompaction (see Supplementary Material).…”
Section: Precipitation Swelling Shrinkage and Compactionmentioning
confidence: 99%
“…This was driven by few samples with thick detritus layers, found with Elytrigia atherica , and in muddy samples on the silty marsh edge (silty pioneer marsh) or swampy areas, all having higher dynamic soil deformation. Additionally, livestock grazing may contribute to lower erosion by compacting the soil (Elschot et al, 2013; Keshta et al, 2020; Marin‐Diaz et al, 2021; Pagés et al, 2018). However in this study, grazing does not seem essential to further reduce surface erosion because similar low erosion values were obtained both in grazed and ungrazed marshes (Appendix S1: Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Sediment grain size was determined with a Malvern Mastersizer 2000. Clay‐silt fraction (<63 μm), hereafter called silt content, has been previously related to clay content and soil cohesion in our marine region (Van Ledden et al, 2004) and for reproducibility it was used in this study instead of the clay fraction alone (e.g., Ford et al, 2016; Lo et al, 2017; Marin‐Diaz et al, 2021). For more information on the other soil fractions obtained see Appendix S1: Table S2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation